ANALYSIS OF THE NEEDS FOR AUGMENTED REALITY DANCE LEARNING MEDIA: LABAN NOTATION MOVEMENT LITERACY FOR JUNIOR HIGH SCHOOL STUDENTS: ANALYSIS OF THE NEEDS FOR AUGMENTED REALITY DANCE LEARNING MEDIA: LABAN NOTATION MOVEMENT LITERACY FOR JUNIOR HIGH SCHOOL STUDENTS - Fatmasari, Siti; Triana, Dinny Devi; Jeon, Jeong OK (International Journal of Performing Arts (IJPA), 2024)
This Research and Development (R&D) study, conducted using the ADDIE model, focused on theAnalysis Phase to address the main learning barrier in Dance Arts in Junior High Schools (SMP):the high difficulty of Phase D students in understanding the Essence of Movement (space, time,energy) and the abstract Laban Notation symbols. Data collected from 20 students and 2 teachers inSerang City indicated an extreme level of difficulty in abstract concepts (85.5% - 87.0%), inverselyproportional to the students' strong interest (92.5%) and readiness for high-tech devices (95.0%) fordigital learning. The goal was to validate the urgency and specify the functional requirements of thesolution. The results confirmed the urgent need for instructional media capable of bridging theabstract (Laban symbols) with the kinesthetic (3D motion). These findings led to the FunctionalSpecifications of Augmented Reality (AR) Media - Motion Literacy. The AR media must specificallyvisualize the interactive and real-time relationship between Laban symbols and 3D motion elements.This AR media is expected to concretize abstract concepts, support the "Create" competency in theIndependent Curriculum, and enable meaningful and enjoyable in-depth learning for 21st-centurylearners. The study concludes with a development plan for the next Design and Development phase.